Physical Efficiency Index (PEI) and injuries after return to play post Covid-19 in Italian Serie A - Giovanelli, M.; Raiola, G.; Palomo, C.; de Baranda, S.; Izzo, R. (Journal of Physical Education and Sport, 2021)
The aim of this study is analyze physical performance in Italian Serie A 2019-2020, after return to play post Covid-19, in the 20 club participants in the championship (n=567 players, age 27.2±1.1, value: 8.12 mln), to understand the causes of injuries that occurred during the last 12 match for the conclusion of the Serie A and variation in high intensity production. The analysis of physical performance is analyzed with SPORTVU OPTICAL TRACKING (STATS PERFORM, CHICAGO, USA) during each football match, from 27 match day (June 2020, after lockdown) to 38 match day (August 2020). Using a semiautomatic video analysis system that has incorporated new parameters able to measure physical efficiency ("Method for game analysis", patented in 2010, PCT/IB2010/002593, K-SPORT UNIVERSAL, MONTELABBATE, ITALY). At the same time we analyzed players absence from each match day for all teams (n=20), to better understand how many injuries the lockdown (3 and a half months) caused over time. Our research relates with a professional Top Level Championship, physical efficiency index and injuries occured during a post Covid-19 period. The championship was suspended due to the Covid-19 emergency on matchday 26 and restart from matchday 27a in June 2020. The percentage of absences due to injury by comparing matchday 27 (post lockdown) and matchday 38 (last season) has showed a statistically significant increase 26% (n=20; p<0.05). Negative correlations was found between PEI (Physical Efficiency Index) and number of injuries occured post lockdown respectively, (n=20, r = -0.25, p > 0.05). For the 2019-20 season there is a total number of absences equal to 2213; compared with the data of the last thirteen seasons , an increase of 6%, statistical meaningfulness, (n=20; p<0.05) is observed compared to the previous season (2018-19). Key performance indicators in this research not predict injuries and they have a low correlation with them. Future studies it`s necessary to have more information on absence of injuires and their relation with performance and techinical/tactical game intelligence. Of course, PEI (Physical Efficiency Index), it`s a good indicator of physical team condition.